SiC power MOSFETs performance, robustness and technology maturity - Castellazzi, Alberto; Fayyaz, Asad; Romano, G.; Yang, Li; Riccio, M.; Irace, A. (Elsevier, 2016)
Relatively recently, SiC power MOSFETs have transitioned from being a research exercise to becoming an industrial reality. The potential benefits that can be drawn from this technology in the electrical energy conversion domain have been amply discussed and partly demonstrated. Before their widespread use in the field, the transistors need to be thoroughly investigated and later validated for robustness and longer term stability and reliability. This paper proposes a review of commercial SiC power MOSFETs state-of-the-art characteristics and discusses trends and needs for further technology improvements, as well as device design and engineering advancements to meet the increasing demands of power electronics.